PERTUMBUHAN DAN PRODUKSI BERBAGAI VARIETAS SORGUM (Sorghum bicolor L.) DENGAN PEMBERIAN PUPUK UREA - Pertiwi, Revy Anggun; Zuhry, Elza; ', Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims to get the best dose of Urea to each sorghum               (Sorghum bicolor L.) varieties. This research used a randomized block design, consisting of 2 factors with 3 replications. The first factor was 4 varieties sorghum, those Kawali, Numbu, Pahat and Mandau. The second factor was 3 levels of Urea treatment (60, 120 and 180 kg Urea/ha). Parameters measured were days to flowering (day), number of segments per plant (node), plant height (cm), stem diameter (cm), number of leaves (stands), panicle length (cm), seed weight per m2 (g) and weight of 1000 seed (g). The mean separation of analysis of variance was tested using Duncan’s multiple range test at 5%. The result indicates that application of 60 kg Urea/ha gave the best result on Pahat and Kawali varieties. Application of 120 kg Urea/ha and 180 kg Urea/ha on Pahat gave the best result compare to Kawali, Numbu and Mandau varieties.   Keywords: Sorghum, Urea, Production.